Management of Advanced Pancreatic Cancer with Gemcitabine Plus Erlotinib: Efficacy and Safety Results in Clinical Practice - Diaz Beveridge, Robert; Alcolea, Vicent; Aparicio, Jorge; Segura, Ángel; García, Jose; Corbellas, Miguel; Fonfría, María; Giménez, Alejandra; Montalar, Joaquin (JOP. Journal of the Pancreas, 2014)
Context The combination of gemcitabine and erlotinib is a standard first-line treatment for unresectable, locally advanced or metastatic pancreatic cancer. We reviewed our single centre experience to assess its efficacy and toxicity in clinical practice. Methods Clinical records of patients with unresectable, locally advanced or metastatic pancreatic cancer who were treated with the combination of gemcitabine and erlotinib were reviewed. Main outcome measures Univariate survival analysis and multivariate analysis were carried out to indentify independent predictors factors of overall survival. Results Our series included 55 patients. Overall disease control rate was 47%: 5% of patients presented complete response, 20% partial response and 22% stable disease. Median overall survival was 8.3 months). Cox regression analysis indicated that performance status and locally advanced versus metastatic disease were independent factors of overall survival. Patients who developed acne-like rash toxicity, related to erlotinib administration, presented a higher survival than those patients who did not develop this toxicity. Conclusions Gemcitabine plus erlotinib doublet is active in our series of patients with advanced pancreatic cancer. This study provides efficacy and safety results similar to those of the pivotal phase III clinical trial that tested the same combination. Image: Overall survival and development of acne-like rash.